Precursor-controlled and template-free synthesis of nitrogen-doped carbon nanoparticles for supercapacitors1. Issue 62 (8th July 2015) - Lv, Li-Ping; Wu, Zhong-Shuai; Chen, Long; Lu, Hao; Zheng, Yi-Ran; Weidner, Tobias; Feng, Xinliang; Landfester, Katharina; Crespy, Daniel
<x xml:space="preserve">Abstract</x> We describe the synthesis of hierarchical porous nitrogen-doped carbon nanoparticles with high specific surface area and specific capacitance for supercapacitors.